2015
DOI: 10.1140/epje/i2015-15119-y
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-body resonance while contacting a rotating superhydrophobic surface

Abstract: We advance a scheme in which a liquid body on a stationary tip in contact with a rotating superhydrophobic surface is able to maintain resonance primarily from stick-slip events. With tip-to-surface spacing in the range 2.73 ≤ h < 2.45 mm for a volume of 10 μL, the liquid body was found to exhibit resonance independent of the speed of the drum. The mechanics were found to be due to a surface-tension-controlled vibration mode based on the natural frequency values determined. With spacing in the range 2.45 ≤ h <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The circumference of the hole then contributes more strongly to the liquid–solid interface area requirement despite it retaining a Cassie wetting state. It should also be noted that the manner in which sessile drops with high contact angles are being constrained on inclines makes them less stable, imbuing them with a propensity to resonate when periodic , or stochastic , perturbations are introduced. We have noticed a similar resonant motion with perturbations, which may be linked to the geometry and composition of the liquid body.…”
Section: Resultsmentioning
confidence: 99%
“…The circumference of the hole then contributes more strongly to the liquid–solid interface area requirement despite it retaining a Cassie wetting state. It should also be noted that the manner in which sessile drops with high contact angles are being constrained on inclines makes them less stable, imbuing them with a propensity to resonate when periodic , or stochastic , perturbations are introduced. We have noticed a similar resonant motion with perturbations, which may be linked to the geometry and composition of the liquid body.…”
Section: Resultsmentioning
confidence: 99%
“…Because the liquid body is subject to this form of perturbation, the surface tension forces involved can drive it to respond dynamically. This is also possible because of compressed air being used here which generates a more stochastic driving impetus as opposed to gravity forces acting alone. , It is noteworthy that resonant behavior had previously been observed in the presence of stochastic perturbations and has been found to occur notwithstanding the small restoring forces developed from SH surfaces. , Although some small extent of this was discerned, the relatively short time period leading to dislodgement does not furnish the means to confirm this.…”
Section: Resultsmentioning
confidence: 79%
“…18,23 It is noteworthy that resonant behavior had previously been observed in the presence of stochastic perturbations 31−33 and has been found to occur notwithstanding the small restoring forces developed from SH surfaces. 32,33 Although some small extent of this was discerned, the relatively short time period leading to dislodgement does not furnish the means to confirm this.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…This is exemplified in recent exercises of energy harvesting using solid structures. , In returning to the case with sessile drops, Chaudhury and Goohpattader demonstrated that drops rolling down a surface with asperities lithographically produced using fibrils with well-defined lengths, cross sections, and spacing could elicit resonance behavior . More recently, an arguably more practical approach was achieved by having the liquid body on a stationary tip coming in contact with a rotating SH drum such that resonance is maintained primarily from stochastic stick–slip events between the liquid and SH surface …”
Section: Introductionmentioning
confidence: 99%
“…23 More recently, an arguably more practical approach was achieved by having the liquid body on a stationary tip coming in contact with a rotating SH drum such that resonance is maintained primarily from stochastic stick− slip events between the liquid and SH surface. 24 Although drops can easily slide down surfaces because of the action of gravity, schemes such as the substrate wetting transformation and air perturbation have been shown to achieve motion up inclines notwithstanding gravity. 12,25 The ability to control the speed of transport of the drop, however, is not possible using these schemes.…”
Section: ■ Introductionmentioning
confidence: 99%